Identify The Basic Soccer Techniques through David Lee Test for Youth Athletes - Yohanes Tampi Wafa; Antonius Tri Wibowo (Journal Of Sport Education (JOPE), 2025)
The This research aims to identify the basic technical skills of players in the Black King Papua club. The basic technical skills analyzed include passing, dribbling, shooting, and controlling. This study uses a quantitative survey method by conducting tests using the David Lee Basic Football Technical Test instrument. The sample consisted of 20 Papuan black king players aged 15-18 years old who took part in a series of tests on the field of SMAN 1 Bae Kudus. The results showed a variation in the player's abilities: 4 players (20%) were in the superior category, 4 players (20%) were in the adequate category, 9 players (45%) were in the poor category, and 3 players (15%) were in the very poor category. Most players have difficulty dribbling, passing, and shooting, which impacts the length of time it takes to complete the test. These findings suggest that players' basic technical skills still need to be improved through a more structured, intensive, and ongoing training program. The results of this research are expected to provide the basis for the development of a more effective coaching program to improve the performance of Papuan Black King players.